Managing Generation Z: Eudaimonic Perspective - Anggraeni, Ade Irma (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
Psychological contracts are dynamic and manifested in the form of employer branding as an understanding of work orientation of Generation Z in the digital era. According to social exchange theory, this study aims to empirically examine the effect of psychological contracts on employee resilience, employee agility and proactive behaviour with eudaimonic workplace wellbeing as a mediating variable. The research was conducted on startup companies in Indonesia. The research model was tested using a structural equation modeling approach. This research contributes to explaining the mechanism for managing expectations of Generation Z through well-being, both intrapersonal and interpersonal aspects. The eudaimonic perspective becomes relevant to achieve alignment of Generation Z work orientation and job characteristics in the digital era.